The dividend puzzle: Testing the signalling hypothesis in an European context - Lobão, Júlio (2020)
Dividend policy continues to puzzle researchers in the discipline of finance. In this paper we test the signalling effects of the dividend payout for a set of European firms that had sustained earnings growth for a minimum period of five years with a decline in the last year. To the best of our knowledge this is the first paper to run and compare the results of several different models including the recently created Simultaneous-Equation Model in its linear and nonlinear forms alongside a simple OLS based estimation. Our results show that managers change dividends to signal equity-scaled earnings prospects instead of asset-scaled earnings. We also find evidence that managers change dividends for signalling previous earnings changes and may distribute dividends to reduce agency costs. These findings suggest that managers identify shareholders as the accepters of dividends and the most direct targets to signalling information.